Condrodita del skarn Loma Marcelo, área de los Cerros Pan de Azúcar y Del corral, Sierras Australes de Buenos Aires - Ballivián Justiniano, Carlos A. (2013)
The occurrence of chondrodite in the Loma Marcelo skarn, Sierras Australes, that constitutes the first mention of a mineral belonging to the humite group in Buenos Aires province, was determined and characterized by petrography, X-ray diffractometry, FTIR spectroscopy and SEMEDS analysis. The purpose of this contribution is to provide a better knowledge of the rich mineralogy of the skarn deposit.